Management of divergent stances as a resource to maintain progressivity and social relationships - Logren, Aija; Ilomäki, Sakari; Ruusuvuori, Johanna (Frontiers in Psychology, 2025)
Previous studies have shown the intersubjective and negotiable nature of stance: interlocutors orient to alignment and adjust their stances to achieve closer alignment. In this article, we study the interplay of three axes of stanceepistemic, deontic and affective stanceand the role their management may have in socially relevant tasks. We describe how the three axes can be simultaneously relevant, taken into account, and dynamically shifted by the participants in a specific sequence of action. The three axes are not always equally aligned or disaligned, but instead divergent: some are aligned at the same time when others are disaligned. Through a case study with two data excerpts, we show how the divergence is an interlocutors' resource to overcome handle the disalignment of some of the stances, and to eventually achieve sufficient alignment in order to be able to proceed their activity. Our data are drawn from the particular institutional context of neurological consultations. where participants' differing roles in terms of the institutional task help to highlight the dynamics of the relationship of the simultaneous axes of stance. We examine the interactants' stance over longer episodes of talk to illustrate their momentary, multimodal interactional work interactants do to display and adjust their stances. The interactants deploy different modalities to address the divergent stances, and further, the multimodal and multifaceted nature of turns enable them to orient to several axes of stance at the same time. Instead of merely taking a stance, the interlocutors manage their stances -both in terms of adjusting the alignment and the balance of the different axes -and thus maintain the social relationship between themselves and the progressivity of the ongoing task.